The Politics of Policy Development to End Obesity for Aboriginal Youth in the Educational Environment - Spurr, Shelley (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
Canada, a country of considerable wealth and resources, has one of the highest standards of living in the world. This country is politically organized as a democracy that is supportive of political and civil freedoms, yet inequalities among certain populations prevail. In general, Aboriginal people experience poorer economic, social, and environmental conditions than those of non-Aboriginal people (Canadian Population Health Initiative, 2005) and lower involvement in political and civil activity. This report also illustrates the inferior health status among Aboriginal people. Within the school system, an educational policy can serve to address an inequality. Hence, the purpose of the paper is to apply the tools outlined by Deborah Stone in her book, Policy Parodox: The Art of Political Decision Making (2002), to demonstrate why I believe school policies should be developed to prevent obesity among Aboriginal youth, to understand the politics of implementing these policies and to analyze and critique the ideas from hypothesized political opponents. Addressing these injustices provides recognition of the racism in present-day educational policy decision-making processes, which can result in more signiﬁcant progress toward an equal and just society which ensures the health of Aboriginal peoples and successive generations.